Pedagogi Etnik Papua: Tren Penelitian Pembelajaran Konteks Lokal Papua - Salman Alparis Sormin; Rudolfus Ruma Bay; Dadang Sundawa; Mubiar Agustin; Dharma Gyta Sari Harahap (Departement of Mathematics Education, 2024)
The research carried out aims to see trends in ethnopedagogical research in Papua that is integrated with local Papuan culture. Classified as Rivew's systematic research, known as Systematic Literature Review (SRL). The article screening process is adjusted to the inclusion criteria according to the research topic which can be used as primary data and secondary data. Next, the data analysis and triangulation process was carried out by paying attention to each component that was used as the basis for the inclusion criteria. The results of the research show that there are various derivations for each component assessed which are spread starting from journal indexers and adjusted to the derivation of learning materials and can be integrated with every aspect and component of local Papuan culture which is oriented towards research trends in the learning process in the Papua region. Based on the findings obtained, it can be concluded that the ethnopedagogical trend is closely related to the development of a learning process that is in accordance with Papuan culture and local wisdom through critical components of inclusion so that through an ethnopedagogical approach it can create a meaningful learning process and have a cooperative learning process orientation.